2023
DOI: 10.1038/s41598-023-31705-6
|View full text |Cite
|
Sign up to set email alerts
|

The utility of airborne hyperspectral and satellite multispectral images in identifying Natura 2000 non-forest habitats for conservation purposes

Abstract: Aerial hyperspectral and multispectral satellite data are the two most commonly used datasets to identify natural and semi-natural vegetation. However, there is no documented analysis based on data from several areas concerning the difference in the classification accuracy of non-forest Natura 2000 habitat with the use of aerial hyperspectral and satellite multispectral data. Also, there is no recommendation, on which habitat can be classified with sufficient accuracy using free multispectral images. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…By considering the results for individual plant communities, it is important to take into account the region, the number of communities, their homogeneity, and the size of vegetation patches, as well as the co-occurrence of similar vegetation classes that can mix spectrally. Vegetation classification is most often subjected to Natura 2000 sites due to legal directives imposing reporting obligations, through which numerous methodologies have been developed to achieve high (>85% OA) accuracy results [40,41]. Wetland areas with abundant plant communities are also of great research interest [42].…”
Section: Discussionmentioning
confidence: 99%
“…By considering the results for individual plant communities, it is important to take into account the region, the number of communities, their homogeneity, and the size of vegetation patches, as well as the co-occurrence of similar vegetation classes that can mix spectrally. Vegetation classification is most often subjected to Natura 2000 sites due to legal directives imposing reporting obligations, through which numerous methodologies have been developed to achieve high (>85% OA) accuracy results [40,41]. Wetland areas with abundant plant communities are also of great research interest [42].…”
Section: Discussionmentioning
confidence: 99%
“…Applying RF (or other machine learning methods) directly to raw satellite multitemporal imagery data from discrete time series is a common method for vegetation and habitat mapping. These time series, typically based on a limited number of cloud-free scenes (e.g., <15%) selected within one year, can be constructed using individual spectral bands or predefined vegetation indices chosen by the authors [6,14,15,17,18,[70][71][72]. In our study we used Sentinel-2 spectral bands discrete time series as input data for RF, avoiding an uncritical pre-selection among various available vegetation indices.…”
Section: Pure Machine Learning Approachmentioning
confidence: 99%
“…These kinds of data are essential for an accurate supervised classification and mapping of plant communities and habitats [5][6][7][8][9][10][11][12][13]. Many studies have demonstrated the potential of direct machine learning applications for raw satellite multitemporal data [14][15][16][17][18]. These models, which we can define as 'Pure Machine Learning' according to Durell et al [19], usually use time series of individual spectral bands or classic vegetation indices, such as the popular NDVI [20], consisting of a limited number of scenes within a single year.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral reflectance for vegetation is very diverse, which makes identification by remote sensing techniques difficult. This problem is particularly important in the case of diverse vegetation with high internal variability, such as wetlands [4], so one of the solutions is to use data with a high spatial and spectral resolution-for example, aerial hyperspectral data (HS) [12][13][14]. In addition, one of the most successful data fusions used to improve mapping quality is a combination of HS and Airborne Laser Scanning (ALS) data [15].…”
Section: Introductionmentioning
confidence: 99%